AN UP-TO-DATE REVIEW ON THE PHYTOCHEMICAL AND PHARMACOLOGICAL ASPECTS OF THE LAWSONIA INERMIS - Ahdania Batool; Kanwal Ashiq; Maryam Khalid; Abubakar Munir; Jamshaid Akbar; Ammara Ahmed (Journal of Animal and Plant Sciences, 2024)
Medicinal plants are extensively used throughout the world to treat a variety of ailments because of their safety, efficacy and affordability. Lawsonia inermis or Henna is commonly used in folk medicine for the cure of several illnesses. Particularly, it is used as a hair and hand dye. The objective of this study is to offer the most recent information regarding the pharmacological and phytochemical profile of the medicinal plant that is backed by evidence. Only indexed research and review papers were taken into account for the present study's data gathering in order to ensure authenticity. Only articles published in English language were considered for this study. To conduct a literature survey, various databases such as Scopus, Google Scholar, PubMed, Science Direct, and MEDLINE were searched without any year limit. The following keywords are used to search the data: “Lawsonia inermis”, “medicinal plants”, “herbs”, “phytochemical”, “pharmacological”, “in vivo“, “in vitro”, “Henna” and “toxicity”. The study's findings showed that the plant contains a variety of potent phytochemicals, including Lawsona, linarigenin, linarisenin, luteolin, lawsochrysin, lawsoniaside, lawsonaphthoate e.tc. The fruits, leaves, and stems of L. inermis have all been demonstrated to have potential pharmacological effects in previous investigations. So far, its antioxidant, cytotoxic, antimicrobial, antiprotozoal, immunomodulatory, hypoglycemic, anti-inflammatory, and anticancer properties have been documented. Even though many aspects of the plant have been researched, additional study is still necessary to completely understand the mechanism behind its pharmacological actions, to confirm its medicinal efficacy, and to justify its usage in traditional medicine.
Keywords: Lawsonia inermis; Henna; Medicinal plants; Traditional Medicine; Pharmacological activities